PENGARUH PENGUNGKAPAN CSR TERHADAP KINERJA KEUANGAN BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - WAHYU WINARDI, IKA Wahyu (Jurnal Akuntansi AKUNESA, 2013)
The purpose of the research is to examine CSR disclosure influence concerningfinancial performance. This research using data 30 banking company of year2011 which registered within BEI. Data collected through secondary dataobservation method. Then doing the classical assumption test, hypothesis test, andregression model using SPSS (ROA, ROE and NIM as dependent variable proksiof financial performance and control variable of CSR). This research resultcouldn’t prove hypothesis before because CSR disclosures has negative effect onthe financial performance. The research proving that investor still shortermoriented and doesn’t consider of CSR disclosure for their investment decision.KEYWORDS: Corporate Social Responsibility, ROA, ROE, NIM